Three-dimensional hydrogel constructs for exposing cells to nanoparticles. Issue 4 (June 2014) - Mansfield, Elisabeth; Oreskovic, Tammy L.; Rentz, Nikki S.; Jeerage, Kavita M.
Abstract In evaluating nanoparticle risks to human health, there is often a disconnect between results obtained from in vitro toxicology studies and those from in vivo activity, prompting the need for improved methods to rapidly assess the hazards of engineered nanomaterials. In vitro studies of nanoparticle toxicology often rely on high doses and short exposure periods due to the difficulty of maintaining monolayer cell cultures over extended time periods as well as the difficulty of maintaining nanoparticle dispersions within the culture environment. In this work, tissue-engineered constructs are investigated as a platform for providing doses of nanoparticles over different exposure periods to cells within a three-dimensional environment that can be tuned to mimic in vivo conditions. Uptake of quantum dots (QDs) by model neural cells was first investigated in a high-dose exposure scenario, resulting in a strong concentration-dependent uptake of carboxyl-functionalised QDs. Poly(ethylene glycol) hydrogel scaffolds with varying mesh sizes were then investigated for their ability to support cell survival and proliferation. Cells were co-encapsulated with carboxyl-functionalised poly(ethylene glycol)-coated QDs at a lower dose than is typical for monolayer cultures. Although the QDs leach from the hydrogel within 24 h, they are also incorporated by cells within the scaffold, enabling the use of these constructs in future studies of cell behaviour and function.